2012
DOI: 10.1159/000343505
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Cerebral White Matter Damage Associated with Cerebral Hyperperfusion and Cognitive Impairment after Carotid Endarterectomy: A Diffusion Tensor Magnetic Resonance Imaging Study

Abstract: Background: Cerebral hyperperfusion after carotid endarterectomy (CEA), even when asymptomatic, often impairs cognitive function. However, conventional magnetic resonance (MR) imaging rarely demonstrates structural brain damage associated with postoperative cognitive impairment. MR diffusion tensor imaging (DTI) is potentially more sensitive for detection of white matter damage. Among the common parameters derived by DTI, fractional anisotropy (FA) is a marker of tract integrity, and mechanical disruption of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 59 publications
0
22
0
5
Order By: Relevance
“…5 Moreover, several studies have found that post-CEA hyperperfusion, even when asymptomatic, causes slight but diffuse damage to the ipsilateral cerebral cortex and white matter. 3,6,7 This damage that occurs after CEA hyperperfusion is a principal cause of the postoperative cognitive impairment observed in 10% of patients following CEA. 3,6,7 Cerebrovascular autoregulatory mechanisms operate through dilation of precapillary resistance vessels that maintain CBF when reductions in cerebral perfusion pressure occur, and this is referred to as stage 1 ischemia.…”
mentioning
confidence: 99%
“…5 Moreover, several studies have found that post-CEA hyperperfusion, even when asymptomatic, causes slight but diffuse damage to the ipsilateral cerebral cortex and white matter. 3,6,7 This damage that occurs after CEA hyperperfusion is a principal cause of the postoperative cognitive impairment observed in 10% of patients following CEA. 3,6,7 Cerebrovascular autoregulatory mechanisms operate through dilation of precapillary resistance vessels that maintain CBF when reductions in cerebral perfusion pressure occur, and this is referred to as stage 1 ischemia.…”
mentioning
confidence: 99%
“…Важной причиной послеоперационного снижения нейрокогнитивных функций считается синдром цере-бральной гиперперфузии, который может иметь место по-сле реконструкции брахицефальных артерий [2,47]. Ча-стота его развития, по данным разных авторов, составляет от 0,2 до 18% [2].…”
Section: кардиология и сердечно-сосудистая хирургия 4 2015unclassified
“…Ча-стота его развития, по данным разных авторов, составляет от 0,2 до 18% [2]. Синдром церебральной гиперперфузии обусловлен значительным повышением кровотока в бас-сейне стенозированной артерии, развивающимся после КЭ и превышающим метаболические потребности мозга [2,47]. T. Nanba и соавт.…”
Section: кардиология и сердечно-сосудистая хирургия 4 2015unclassified
See 1 more Smart Citation
“…T. Nanba и соавт. [27] при помощи МРТ фиксировали структурные изменения белого вещества ГМ в виде зон лейкоареоза, а с помощью пред-и послеоперационного тестирования -нарушения КФ. Они уделяли особое внимание синдрому гиперпер-фузии как причине нарушений КФ у пациентов сразу по-сле операции на сонных артериях.…”
unclassified